Barriers to free antiretroviral treatment access among kothi-identified men who have sex with men and aravanis (transgender women) in Chennai, India. - Chakrapani, Venkatesan; Newman, Peter A; Shunmugam, Murali; Dubrow, Robert (AIDS care, 2011)
The Indian government provides free antiretroviral treatment (ART) for people living with HIV. To assist in developing policies and programs to advance equity in ART access, we explored barriers to ART access among kothis (men who have sex with men [MSM] whose gender expression is feminine) and aravanis (transgender women, also known as hijras) living with HIV in Chennai. In the last quarter of 2007, we conducted six focus groups and four key-informant interviews. Data were explored using framework analysis to identify categories and derive themes. We identified barriers to ART access at the family/social-level, health care system-level, and individual-level; however, we found these barriers to be highly interrelated. The primary individual-level barrier was integrally linked to the family/social and health care levels: many kothis and aravanis feared serious adverse consequences if their HIV-positive status were revealed to others. Strong motivations to keep one's HIV-positive status and same-sex attraction secret were interconnected with sexual prejudice against MSM and transgenders, and HIV stigma prevalent in families, the health care system, and the larger society. HIV stigma was present within kothi and aravani communities as well. Consequences of disclosure, including rejection by family, eviction from home, social isolation, loss of subsistence income, and maltreatment (although improving) within the health care system, presented powerful disincentives to accessing ART. Given the multi-level barriers to ART access related to stigma and discrimination, interventions to facilitate ART uptake should address multiple constituencies: the general public, health care providers, and the kothi and aravani communities. India needs a national policy and action plan to address barriers to ART access at family/social, health care system, and individual levels for aravanis, kothis, other subgroups of MSM and other marginalized groups.
Keywords: Adult; Anti-Retroviral Agents; Female; Focus Groups; Health Knowledge, Attitudes, Practice; Health Services Accessibility; HIV Infections; Homosexuality, Male; Humans; India; Male; National Health Programs; Prejudice; Qualitative Research; Social Stigma; Transsexualism